Osteología de Paralichthys adspersus “lenguado” en la región La Libertad, Octubre 2015 – Marzo 2016. - Rubio Rodríguez, Katherine Rossemary (2016)
To bone is the foundation upon which the definition of large groups is based and the discussion of affinities and differences between them. The sole Paralichthys adspersus is a representative of the family Paralichthydae, belongs to the order Pleuronectiformes. The objectives of this work were the identification and description of the osteology of Paralichthys adspersus "sole" from the La Libertad region. Identification of each of the bony structures that make up the skeleton of P. adspersus "sole" .Description of each one Of the bony structures that make up the skeleton of P. adspersus "sole". The Chirichigno key was used to identify the species, cuts were made by removing scales, viscera and skin, using boiled water to remove the remaining remains attached to the bone. P. adspersus has the general characteristics that have been given for the family to which it belongs. The neurocranium is asymmetrical._x000D_ Key words: Sole, Osteology, Pleuronectiformes, P. adspersus.